CPW based Band Pass Filter Using DGS for ISM Band Applications - S. Jalaja, Mrs.; V. Prithivirajan, Dr; Gajalakshimi, K; Chitra, S; Nithya, R (International Journal of Engineering and Technology, 2018)
The design and simulation of coplanar waveguide (CPW) bandpass filter (BPF) has been described in this paper. It mainly focuses on Defected Ground Structure (DGS), where U-shaped DGS with open stub in transmission line has been introduced. By etching the DGS pattern in ground and transmission will change the distribution of inductance and capacitance to produce filtering effect. This paper also discusses about the influence of geometrical parameter l for the improvement in the frequency response of bandpass filter. As increasing the dimension of the geometric parameter l shift the center frequency to the higher frequencies. This filter offers a bandwidth of 1.65 GHz with passband ranging from 2.1 GHz to 3.75 GHz with a stopband rejection is about -28 dB.Â Â